Informa Ya Soja 2022/23. Resultados de la red de ensayos de soja del centro-sur de Santa Fe 2022/23 - Enrico, Juan Martin; Bacigaluppo, Silvina (Estación Experimental Agropecuaria Oliveros, INTA, 2023)
Ficha técnica